Effectiveness of the Butterfly Hug Method to the Level of Mental Health Status of Senior Citizens Living in a Selected Healthcare Facility: Basis for Adjunct Therapy - Cagaoan, Mariah Samantha F; Dayrit , Antoinette Celine D; Vega, Allyson Claire R. Dela; Flores, Michael John V (Al-Hijrah Indonesia, 2023)
The Butterfly Hug Method is a non-pharmacological therapeutic intervention that is used to return the hyperaroused mind into a relaxed state. However, a small number of studies have been conducted to examine the effects of the butterfly hug method to the mental health status of senior citizens. This study aimed to determine the Effects of the Butterfly Hug Method on the Mental Health Status of Senior Citizens. The study employed quantitative true-experimental research design. The study was conducted in a selected healthcare facility located in Caloocan City, Philippines. Simple random sampling was utilized to select and divide the participants into two groups, experimental group and control group. The sample was composed of 10 participants. Data were collected using the adopted tools, Patient Health Questionnaire - 9 (PHQ-9) and Generalized Anxiety Disorder - 7 (GAD-7). Data collected were analyzed using descriptive statistics, particularly mean and standard deviation. Inferential statistics was utilized, particularly using paired t-test and independent sample t-test. There is no significant difference between the post test results of the control group and the experimental group. Both interventions, Standard of Care (Physical Activity) and Butterfly Hug Method, were effective in reducing the levels of anxiety and depression in senior citizens. Both interventions were able to reduce the level of anxiety and depression in senior citizens. Regardless that there is no significant difference between the effectiveness of the standard of care in the control group and the butterfly hug method in the experimental group, it has been established that the score and level of depression and anxiety of the participants in the experimental group was reduced. Thus, the Butterfly Hug Method is beneficial to senior citizens in improving the levels of their mental health status.